2014
DOI: 10.1016/j.ajo.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Optic Disc Hemorrhage in the Low-Pressure Glaucoma Treatment Study

Abstract: In this cohort of Low-Pressure Glaucoma Treatment Study patients, migraine, baseline narrower neuroretinal rim width, low systolic blood pressure and mean arterial ocular perfusion pressure, and use of systemic β-blockers were risk factors for disc hemorrhage detection. Randomization assignment did not influence the frequency of disc hemorrhage detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 45 publications
5
55
1
1
Order By: Relevance
“…Brimonidine use was also associated with a trend toward less frequent occurrence of disc hemorrhages. 52 The counter view that the study did not demonstrate the neuroprotective effect of brimonidine but rather the deleterious effect of timolol seems unlikely. First the disease progression in the timolol arm of the study (39% in 3 years) was comparable to the untreated arm of the Collaborative NTG Study (35%).…”
Section: Text Of Reviewmentioning
confidence: 91%
“…Brimonidine use was also associated with a trend toward less frequent occurrence of disc hemorrhages. 52 The counter view that the study did not demonstrate the neuroprotective effect of brimonidine but rather the deleterious effect of timolol seems unlikely. First the disease progression in the timolol arm of the study (39% in 3 years) was comparable to the untreated arm of the Collaborative NTG Study (35%).…”
Section: Text Of Reviewmentioning
confidence: 91%
“…23 The Low-Pressure Glaucoma Treatment Study showed that a history of migraine, narrower baseline neuroretinal rim width, the use of systemic β-blockers, low mean systolic blood pressure, and low mean arterial OPP were risk factors for the occurrence of disc hemorrhage. 24 In addition, platelet function has been shown to be associated with disc hemorrhage in patients with NTG because delayed platelet aggregation can cause prolonged bleeding, delaying absorption. 25 Thus, the occurrence of disc hemorrhage is a significant risk factor for glaucoma progression, whereas migraine, low OPP, and reduced platelet function are also related.…”
Section: Disc Hemorrhagementioning
confidence: 99%
“…Thus, we can conclude that other mechanisms exist for retinal ganglion cell death. A reduction or dysregulation of blood supply to the optic nerve is one potential mechanism in which local and/or systemic conditions, such as systemic hypotension [57][58][59] , would favor an ischemic insult of the optic nerve [60] . Other potential damage pathways are increased apoptosis (increased neurotoxicity, neurotrophin depletion) and oxidative stress, among others.…”
Section: Metabolomics In Glaucomamentioning
confidence: 99%